Mentoring Student Nurses – Are Nurses Prepared, Recognized, and Supported to Teach Nursing Students in Clinical Settings? - Ali, Yasir; Khan, Saeeda; Mustafa, Ghulam; Hussain, Khadim; Akhter, Ambreen (Indus Journal of Bioscience Research, 2025)
Background: Clinical teaching and supervision of undergraduate nursing students is one continuous, high volume, high impact responsibility of registered nurses at clinical environment. Objective: The objective of the study was to identify the level of preparedness, recognition and support in their role to teach and supervise the nursing students. Methodology: A cross-sectional study was conducted at a tertiary care hospital in Karachi, Pakistan, from July to October, 2023. The convenient sampling technique was used to collect data followed by written informed consent, calculated sample size was 81. All the RN, GBSN, Post-RN BSN, MSN nurses having valid PNC license and working at clinical setting were included and those nurses who were already involved in teaching were excluded. Data were analyzed via SPSS version 26.0. Results: Among all participants, 51% (n=41) were aged between 25-45 years, 48.1% (n=39) were males and 51.9% (n=42) were females participated in the study. Out of the total participants, 37.0% (n=30) of participants from Post RN BSN and 4.9% (n=4) of the participants from Master of Science in Nursing (MSN). 43.2% (n = 35) was the number of respondents who had previous experience of supervising. Conclusion: The current model of clinical placement has to be revised due to the growing difficulty of the practice environment, the rise in need of the nursing student’s professional growth and the hopes placed on RNs.